2021
DOI: 10.3390/foods10020468
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-I Converting Enzyme Inhibition and Antioxidant Activity of Papain-Hydrolyzed Camel Whey Protein and Its Hepato-Renal Protective Effects in Thioacetamide-Induced Toxicity

Abstract: Papain hydrolysis of camel whey protein (CWP) produced CWP hydrolysate (CWPH). Fractionation of CWPH by the size exclusion chromatography (SEC) generated fractions (i.e., SEC-F1 and SEC-F2). The angiotensin- converting- enzyme inhibitory activity (ACE-IA) and free radical scavenging actions were assessed for CWP, CWPH, SEC-F1, and SEC-F2. The SEC-F2 exerted the highest ACE-IA and scavenging activities, followed by CWPH. The protective effects of CWPH on thioacetamide (TAA)-induced toxicity were investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…These peptides exerted significant antioxidant activities and inhibition of the angiotensin-converting enzyme. The smaller size fraction (SEC-1) exerted powerful hepatoprotective, antihyperlipidemic, and antioxidant effects in thioacetamide-induced hepatotoxicity [ 24 ]. In a recent publication of our research group, we reported the protective effects of CM treatment on the histological and biochemical features of NAFLD induced by HFD-C in rats [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These peptides exerted significant antioxidant activities and inhibition of the angiotensin-converting enzyme. The smaller size fraction (SEC-1) exerted powerful hepatoprotective, antihyperlipidemic, and antioxidant effects in thioacetamide-induced hepatotoxicity [ 24 ]. In a recent publication of our research group, we reported the protective effects of CM treatment on the histological and biochemical features of NAFLD induced by HFD-C in rats [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The peculiar composition of CM was associated with beneficial effects in NAFLD including decreased appetite, diminished cholesterol absorption from the gut, and reduced fat accumulation in the liver. Additionally, CM treatment counteracted hyperglycemia, IR, oxidative stress, and inflammation in experimental models of DM [22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, Ca-CN was explicitly high in some essential ones, e.g., histidine, isoleucine, leucine, lysine, phenylalanine and valine levels [43]. Milk proteins are the main source of a range of biologically active peptides, essential amino acids, and the appearance of their specific physiological characteristics may have nutritional significance, which is another aspect of their nutritional value [44][45][46][47][48][49][50][51][52]. These results are similar to those of Karkos et al [53], who noticed significantly greater body weight when supplementing Spirulina into the poultry diet than the control.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of whey protein hydrolysate was estimated by ABTS (2,20azino-bis (3-ethylbenzothiazoline 6-sulfonic acid) assay (Merck KGaA, Darmstadt, Germany) and according to Abdel-Hamid et al [34] and Osman et al [42]. The ABTS+ solution was prepared with final concentrations of 7 mM ABTS and 2.45 mM potassium persulfate.…”
Section: Abts-assaymentioning
confidence: 99%